Isolation, Characterization of Bamboo Leaf Flavonoids by Size Exclusion Chromatography and Their Antioxidant Properties. Issue 9 (8th August 2022) - Ye, Shuhuan; Pan, Fupeng; Yao, Linna; Fang, Hailing; Cheng, Yaqian; Zhang, Zixuan; Chen, Yongjian; Zhang, Ailian
Abstract: The utilization of bamboo industry exhibits varied but still needs to be improved. Bamboo leaf flavonoid (BLF) is an important resource of bamboo which has become a research focus. However, the isolation and purification techniques of four flavonoid carbon glycosides (orientin, isoorientin, vitexin, and isovitexin) from BLF were still confronted with difficulties due to their complex and similar structures, which obstructed the development of bamboo utilization. In this article, a purification technology of four flavonoid carbon glycosides from BLF by Sephadex LH‐20 was improved. The results were evaluated by HPLC and pharmacological activity. Specifically, the eluent, flow rate, and loading amount were investigated, respectively. According to the results, the eluent would dominate the isolation effect among three factors. High concentration of isoorientin and four flavonoid carbon glycosides would be obtained under the optimized condition (The eluent was 70 % methanol, the loading amount was 1.5 g, and the flow rate was 0.5 mL/min). Meanwhile, the link between flavonoid carbon glycosides content and their antioxidant activity in vitro was also revealed. Overall, the results suggested that BLF may serve as potential functional food additives and medicine. Abstract :